Design and Implementation of a Low-Cost Water Quality Monitoring System for Aquaculture in Indonesia - Kairat Kairbekov; Dauren Sarsenov; Zhanna Kairbekova (Proceeding of the International Conferences on Engineering Sciences, 2025)
Aquaculture is a significant industry in Indonesia, but water quality management remains a challenge, impacting fish health and productivity. This paper presents a low-cost, IoT-based water quality monitoring system designed for small-scale aquaculture operations. The system continuously measures pH, temperature, dissolved oxygen, and turbidity, providing farmers with real-time data via a mobile application. Field trials in Java demonstrate the system's effectiveness in maintaining optimal water conditions, reducing fish mortality, and increasing yield. The study suggests that affordable, technology-driven solutions can substantially benefit the aquaculture sector in Indonesia.